Examining CO2 as an Additive for Solid Electrolyte Interphase Formation on Silicon Anodes. Issue 3 (18th March 2021) - Hopkins, Emma J.; Frisco, Sarah; Pekarek, Ryan T.; Stetson, Caleb; Huey, Zoey; Harvey, Steven; Li, Xiang; Key, Baris; Fang, Chen; Liu, Gao; Yang, Guang; Teeter, Glenn; et al.
Abstract : We demonstrate that the addition of CO2 to a standard 1.0 M LiPF6 3:7 wt% ethylene carbonate:ethyl methyl carbonate electrolyte results in the formation of a thinner insoluble solid electrolyte interphase (SEI) that is dominated by the presence of LiF. In contrast, cells without CO2 result in a thicker insoluble SEI layer containing more organic constituents. The CO2 is incorporated in the dimethyl carbonate soluble part of the SEI composed primarily of polymeric poly(ethylene oxide) (PEO) on the surface of a thin inorganic layer. This combination of properties from CO2 addition provides an improved cycling performance through the reduction of irreversible side reactions, leading to higher coulombic efficiency. The results indicate that CO2 incorporates into the SEI and plays a role similar to additives like fluorinated ethylene carbonate and vinylene carbonate with respect to polymeric components.